Monoterpenes in Plants- a mini review (Asian Journal of Plant Biology, 2013)
Monoterpenes are abundant chemicals in plants that are formed by a multitude of enzymes and present a challenge both in identification and understanding the synthetic enzymes involves in their formation and fate. They are especially abundant in fragrance-producing plants. The enyme that produce them are numerous but several key enzymes have been identified and are discussed in this short review.
Keywords: Monoterpenes; Plants; Linalool